A Novel Polyamine Allosteric Site of SpeG from Vibrio cholerae Is Revealed by Its Dodecameric Structure. Issue 6 (27th March 2015) - Filippova, Ekaterina V.; Kuhn, Misty L.; Osipiuk, Jerzy; Kiryukhina, Olga; Joachimiak, Andrzej; Ballicora, Miguel A.; Anderson, Wayne F.
Abstract: Spermidine N -acetyltransferase, encoded by the gene speG, catalyzes the initial step in the degradation of polyamines and is a critical enzyme for determining the polyamine concentrations in bacteria. In Escherichia coli, studies have shown that SpeG is the enzyme responsible for acetylating spermidine under stress conditions and for preventing spermidine toxicity. Not all bacteria contain speG, and many bacterial pathogens have developed strategies to either acquire or silence it for pathogenesis. Here, we present thorough kinetic analyses combined with structural characterization of the VCA0947 SpeG enzyme from the important human pathogen Vibrio cholerae . Our studies revealed the unexpected presence of a previously unknown allosteric site and an unusual dodecameric structure for a member of the Gcn5-related N -acetyltransferase superfamily. We show that SpeG forms dodecamers in solution and in crystals and describe its three-dimensional structure in several ligand-free and liganded structures. Importantly, these structural data define the first view of a polyamine bound in an allosteric site of an N -acetyltransferase. Kinetic characterization of SpeG from V . cholerae showed that it acetylates spermidine and spermine. The behavior of this enzyme is complex and exhibits sigmoidal curves and substrate inhibition. We performed a detailed non-linear regression kinetic analysis to simultaneously fit families of substrate saturation curves to uncover a simple kinetic mechanism that explains the apparent complexity of this enzyme. Our results provide a fundamental understanding of the bacterial SpeG enzyme, which will be key toward understanding the regulation of polyamine levels in bacteria during pathogenesis. Graphical abstract: Highlights: Spermidine N -acetyltransferase (SpeG) prevents bacterial polyamine toxicity. The dodecameric three-dimensional structure of SpeG revealed an unknown polyamine allosteric site. SpeG acetylates spermidine/spermine using a bireactant random steady-state mechanism. SpeG has the first-described Gcn5-related N -acetyltransferase structure with 12 active and 12 allosteric sites.